The Effect of NPK Fertilizer and Gobest ZPT on the Growth of Chili Plants (Capsicum frutescens L.) - Dimas Indra Kurniawan; M. Abror (Demeter: Journal of Farming and Agriculture, 2025)
Abstract. This study aims to determine the effect of NPK and ZPT Gobest fertilizers on the growth of cayenne pepper plants (Capsicum frutescens L.). The experiment was carried out using a Group Random Design (RAK) with two factors, namely the dose of NPK fertilizer (100 kg/ha, 150 kg/ha, and 200 kg/ha) and the concentration of ZPT Gobest (1 ml/liter, 2 ml/liter, and 3 ml/liter) which was repeated for three replicates. The parameters observed included plant height, number of leaves, leaf area, and number of branches. The results showed that the application of 200 kg/ha NPK fertilizer and 2 ml/liter ZPT Gobest had the best influence on plant vegetative growth, such as plant height and number of leaves, leaf area, and number of branches.